The Effect of E-Performance and E-Government on the Employee Performance with Motivation as an Intervening - Antiq Novinda Damayanti (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Human Resources is one of the important elements in an organization. Organizations need to pay attention to how to improve employee performance. Currently, the large number of employees (ASN) is a big obstacle in realizing good governance because the efficiency and effectiveness of employee performance is difficult to measure. Because of the difficulties in measuring the performance of public organizations, E-Performance and E-Government have been implemented. The main reason for implementing this application is because the government indicates that there are unscrupulous employees whose work is not in accordance with their main duties, functions and workload, apart from that there are also officials whose positions do not meet the required competence and capacity. E-Performance and E-Government are web-based applications that are used to assess and measure employee performance based on job analysis and workload analysis, as well as being the basis for calculating work performance. With the existence of E-Performance and E-Government, it is hoped that it can motivate employees to improve their performance. The analysis used in this research is a quantitative method using the SPSS Version 24 and Smart PLS 3.0 programs. The analysis technique in this research is Structure Equation Modeling (SEM) using Partial Least Square (PLS) with a significance of 5%. The research results show that E-Performance and E-Government increase employee motivation and performance. Employees feel that it is made easier, thereby creating motivation to improve organizational performance. With good motivation, employees will feel happy and enthusiastic at work, thereby increasing significant development and growth in the organization.